Pemanfaatan Agentic AI Model Chatgpt dari Openai untuk Meningkatkan Efektivitas Pengambilan Keputusan Operasional di CV. Central Telematika Sempurna - Robertus Robby Julianto Simonaji; Maclaurin Hutagalung (Economic Reviews Journal, 2025)
The digital transformation era compels organizations to adopt intelligent technologies to enhance operational efficiency and decision-making effectiveness. One such emerging technology is Agentic AI, particularly ChatGPT by OpenAI, which operates autonomously and adapts to dynamic work contexts. This study aims to explore how the implementation of Agentic AI supports operational decision-making at CV. Central Telematika Sempurna, assess its impact on work efficiency, evaluate the leadership’s role in the adoption process, and uncover employee perceptions regarding its use. Employing a qualitative approach with an exploratory case study design, data were collected through in-depth interviews with 5 informants across various divisions, supplemented by non-participant observation and internal documentation. Thematic analysis was conducted using NVivo software, involving open coding, categorization, and interpretative synthesis. The findings are expected to offer deep insights into the contribution of Agentic AI in enhancing operational decision-making and to support strategic technology management in digitally transforming organizations.